2018
DOI: 10.5463/dcid.v29i1.664
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions, Attitudes and Involvement in Interventions for Autism Spectrum Disorders in Sarawak, Malaysia

Abstract: Purpose: This study explores and compares perspectives of educators and parents regarding interventions used in managing Autism Spectrum Disorder (ASD) in Sarawak, Malaysia. Information on parental desires and limitations when selecting and maintaining management will aid in the development of strategies for ASD educators to work effectively with parents and caregivers, and vice versa.Method: This qualitative research employed traditional question and answer interviews with 7 ASD educators and 30 parents. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The prevalence we found was lower compared to other studies (ranging from 72 to 93.7%) in children with ASD ( 4 , 6 , 63 ). This difference may be due to higher stigma and limited awareness about ASD and mental illness in Malaysia ( 59 , 60 , 64 ), causing caregivers to report fewer symptoms their child might be having.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence we found was lower compared to other studies (ranging from 72 to 93.7%) in children with ASD ( 4 , 6 , 63 ). This difference may be due to higher stigma and limited awareness about ASD and mental illness in Malaysia ( 59 , 60 , 64 ), causing caregivers to report fewer symptoms their child might be having.…”
Section: Discussionmentioning
confidence: 99%
“…Both parents and children faced time constraints to commit to the CFT as they always have a packed schedule. This challenge of the time constraint is supported by Teo and Lau’s [ 47 ] study and Moroz’s [ 48 ] research. It is an issue commonly faced by parents with special needs children in Malaysia and the USA.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noticeable that their weekly CFT homework is impeded by children’s packed schedule of after-school activities and the emphasis on academic-related activities. Parents’ emphasis on the academic performance of their children reflects the collectivist culture, where children’s ability to compete with others is often highlighted [ 47 ]. This speaks to the different value practices in the macro-system of the family members that impact the special needs children’s functioning in interventions as proposed in the Bronfenbrenner Ecological Framework [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, both parents (participants or guests) or both parties’ children were pressed for time to commit to the CFT because their schedules were always full. Both studies by [ 30 ] and [ 31 ] supported the time constraint problem. It is a problem that parents of special needs children in Malaysia and the United States often confront.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that the parents placed a high value on their children’s academic performance. This mindset is mirrored in East Asian culture, where parents value their children’s ability to compete with others [ 30 ]. This demonstrates the various values practised by family members in the macro-system, which can impact the functioning of special needs children in the intervention, as proposed by Bronfenbrenner’s Ecological Framework [ 36 ].…”
Section: Discussionmentioning
confidence: 99%